Meaning and its Impact on Aesthetic Reception - Abdul Hussein Al-Khafaji, Zeena Ghani (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT It is natural that the aim of this research is to achieve the critical thought with reference to the characteristics of each literary school in terms of (reception) concept and show reasons of comparing this concept between the theory pioneers and significant figures of our criticism science like: Al-Jahiz, Abdulqaher Al-Jurjani and Al-Qartajni. Perhaps some of the factors that forced us to demonstrate the opinions of those critics are what we found within the contents of the new theory regarding the thought that has no reference except in our criticism credit and therefore, meaning.